Effectiveness of a multidisciplinary intervention in breast cancer survivors - Correia,Tânia (2016)
The number of survivors of breast cancer has been increasing due to advances in early detection and treatment of breast cancer. The multidisciplinary intervention has been shown to be effective in breast cancer survivors. This study aims to implement and evaluate a multidisciplinary intervention program in women survivors of breast cancer. A sample of 19 breast cancer survivors divided into two groups: 9 were proposed intervention and 10 without intervention. Both groups were monitored within two different moments: before and after intervention. The assessments instruments used were Organization for Research and Treatment of Cancer Quality of Life Questionnaire of the European with the Supplementary Questionnaire Breast Cancer Module (EORTC QLQ-C3O and BR-23), Hospital Anxiety and Depression Scale (HADS), Cancer Coping Questionnaire (CCQ), Self-Concept Clinical Inventory (ICAC) and Fear of Progression Questionnaire (FoP-Q). Experimental group showed significant increase of physical scale of quality of life domain. In control group showed significant decrease of interpersonal scale and significant increase of total self-concept. Multidisciplinary program implemented reveal effective on quality of life increase of Portuguese women's breast cancer survivors.